أصول النظرية السياقية الحديثة عند علماء العربية ودور هذه النظرية في التوصل إلى المعنى - يحيا مالك (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يلقي هذا البحث الضوء على أصول النظرية السياقية الحديثة عند علماء اللغة الغربيين ومن تبعهم من علماء العربية المحدثين ، ويبين أن علماء العربية لم يكونوا بعيدين عن إدراك وظيفة السياق ودلالته ، فقد استعان علماء القرآن الكريم والأصوليون بشقي السياق في فهم دلالة النصوص الشرعية ، كما ربط عبد القاهر الجرجاني فصاحة الكلمة بسياقها اللغوي والتركيب الذي قيلت فيه ، عند حديثه عن نظرية النظم ، وربط الكلام بمقام استعماله. وأن الخليل وتلميذه سيبويه قد اعتمدا على السياق اللغوي في بيان معنى التركيب ودلالته ، واستعانا بطرق الأداء اللغوي المصاحبة للنطق بالعبارة ، كالوقف والنبر والتنغيم. وأما اعتمادهم على سياق الحال فيتضح من استعانتهم بإرادة المتكلم والمخاطب في تعيين معنى التركيب، واهتمامهم بملابسات الحال في التوجيه النحوي ، والحكم على التركيب بالصحة أو الإحالة ، وتسويغ الحذف استناداً على دلالة الحركة الجسمية ، والحواس الخمس ، وباقي عناصر سياق الحال. وهكذا تلتقي تطبيقات الخليل وتلميذه سيبويه مع أحدث الاتجاهات اللغوية مع تباعد الزمن والشقة. This paper highlights the origin of the use theory of western linguists and their followers of Modern Arab linguists. It shows that the Arab grammarians were not far away from understanding the role of context: the Quran interpreters depended on context to explain the meaning of verses, and when speaking about compositionality, Abdul Qaher aljurjani connected the clarity of the word with the context and the structure in which it is used. It also shows that al–khaleel and Sibawiyeh depend on the linguistic context to explicate the content and reference of expressions and extending it to explain sentence meaning. They depend on performance indices such as pause, stress and intonation. Their dependence on the context of situation is clear form their use of the speaker–hearer’s intention to decide the utterance meaning, as well as their interest in the pragmatic ambiguity and judging an expression to be false or true, and allowing for deletion, depending on body gestures, the five senses and the rest of the contextual factors. Thus al–khaleel’s and Sibawiyeh’s applications meet with the linguistic, though they are further in time and space.